Different adaptations of dopamine release in Nucleus Accumbens shell and core of individual alcohol drinking groups of mice. (15th September 2020) - Liu, Yutong; Montgomery, Sarah E.; Juarez, Barbara; Morel, Carole; Zhang, Song; Kong, Yimeng; Calipari, Erin S.; Nestler, Eric J.; Zhang, Lu; Han, Ming-Hu
Abstract: Alcohol use disorder (AUD) places a tremendous burden on society, with approximately two billion alcohol users in the world. While most people drink alcohol recreationally, a subpopulation (3–5%) engages in reckless and compulsive drinking, leading to the development of AUD and alcohol dependence. The Ventral Tegmental Area (VTA)-Nucleus Accumbens (NAc) circuit has been shown to encode rewarding stimuli and drive individual alcohol drinking behavior. Our previous work successfully separated C57BL/6J isogenic mice into high or low alcohol drinking subgroups after a 12-day, two-bottle choice voluntary alcohol access paradigm. Electrophysiological studies revealed that low alcohol drinking mice exhibited elevated spontaneous and burst firing properties of their VTA dopamine (DA) neurons and specifically mimicking this pattern of activity in VTA-NAc neurons in high alcohol drinking mice using optogenetics decreased their alcohol preference. It is also known that VTA DA neurons encode the salience and rewarding properties of external stimuli while also regulating downstream dopamine concentrations. Here, as a follow-up to this study, we utilized Fast Scan Cyclic Voltammetry (FSCV) to examine dopamine release in the NAc shell and core between alcohol drinking groups. We observed dynamic changes of dopamine release in the core of high drinking mice, but failed to see widely significant differences of dopamine release in the shell of both groups, when compared with ethanol-naive controls. Overall, the present data suggest subregion-specific differences of evoked dopamine release in the NAc of low and high alcohol drinking mice, and may provide an anatomical substrate for individual alcohol drinking behavior. This article is part of the special issue on Stress, Addiction and Plasticity. Highlights: Mice were split into groups based on their low and high alcohol drinking behaviors. Dopamine release between alcohol drinking mice varied in the NAc core and the shell. High alcohol drinking mice exhibited significant evoked dopamine release in NAc core.